Derivative Sampling Expansions for the Linear Canonical Transform: Convergence and Error Analysis (Journal of Computational Mathematics, 2019)
In recent decades, the fractional Fourier transform as well as the linear canonical transformbecame very efficient tools in a variety of approximation and signal processing applications.There are many literatures on sampling expansions of interpolation type forband-limited functions in the sense of these transforms. However, rigorous studies on convergenceor error analysis are rare. It is our aim in this paper to establish samplingexpansions of interpolation type for band-limited functions and to investigate their convergenceand error analysis. In particular, we introduce rigorous error estimates for thetruncation error and both amplitude and jitter-time errors.